PENERAPAN ALGORITMA MAX-MINER UNTUK ANALISIS POLA BELANJA KONSUMEN (STUDI KASUS KAFELOAJA) - Marsia Marsia; Jeanny Pragantha; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2020)
This application is used to produce combination meal for Kafeloaja in order to give the owner advices to make decision in business. In this application the method used are Max-Miner and Market Basket Analysis. Max-Miner is used to find frequent maximal itemset and the result is used to formulate association rule in Market Basket Analysis. The result of this program are menu combinations that can be used by owner to be added as new combination meal.